Interactive Persuasive Systems: A Perspective on Theory and Evaluation. Issue 3 (3rd March 2016) - Spagnolli, Anna; Chittaro, Luca; Gamberini, Luciano
Abstract : Interactive systems are increasingly used in a growing number of domains to encourage users to perform certain actions or take a certain position toward a given subject. This article offers a perspective on interactive persuasive systems that emphasizes theories and concepts that can guide their design and evaluation. The goal is not to champion a theoretical model over others or to compare the effectiveness of different persuasive strategies but rather to depict the current conceptual landscape in this field and highlight emerging concepts and positions that have recently appeared in it. The article includes a discussion of some representative, general, and domain-specific constructs that can be used to evaluate the effectiveness of interactive persuasive systems.